Hepatocyte‐specific Ptpn6 deletion promotes hepatic lipid accretion, but reduces NAFLD in diet‐induced obesity: Potential role of PPARγ. Issue 5 (1st April 2014) - Xu, Elaine; Forest, Marie‐Pier; Schwab, Michael; Avramoglu, Rita Kohen; St‐Amand, Emmanuelle; Caron, Annabelle Z.; Bellmann, Kerstin; Shum, Michaël; Voisin, Gregory; Paquet, Marilene; Montoudis, Alain; Lévy, Emile; et al.
<x xml:space="preserve">Abstract</x> Hepatocyte‐specific Shp1 knockout mice (Ptpn6H‐KO) are protected from hepatic insulin resistance evoked by high‐fat diet (HFD) feeding for 8 weeks. Unexpectedly, we report herein that Ptpn6H‐KO mice fed an HFD for up to 16 weeks are still protected from insulin resistance, but are more prone to hepatic steatosis, as compared with their HFD‐fed Ptpn6f/f counterparts. The livers from HFD‐fed Ptpn6H‐KO mice displayed 1) augmented lipogenesis, marked by increased expression of several hepatic genes involved in fatty acid biosynthesis, 2) elevated postprandial fatty acid uptake, and 3) significantly reduced lipid export with enhanced degradation of apolipoprotein B (ApoB). Despite more extensive hepatic steatosis, the inflammatory profile of the HFD‐fed Ptpn6H‐KO liver was similar (8 weeks) or even improved (16 weeks) as compared to their HFD‐fed Ptpn6f/f littermates, along with reduced hepatocellular damage as revealed by serum levels of hepatic enzymes. Interestingly, comparative microarray analysis revealed a significant up‐regulation of peroxisome proliferator‐activated receptor gamma (PPARγ) gene expression, confirmed by quantitative polymerase chain reaction. Elevated PPARγ nuclear activity also was observed and found to be directly regulated by Shp1 in a cell‐autonomous manner. Conclusion: These findings highlight a novel role for hepatocyte Shp1 in the regulation of PPARγ and hepatic lipid metabolism. Shp1 deficiency prevents the development of severe hepatic inflammation and hepatocellular damage in steatotic livers, presenting hepatocyte Shp1 as a potential novel mediator of nonalcoholic fatty liver diseases in obesity. (Hepatology 2014;59:1803–1815)